Sustainability-Oriented Practices: The Impact of Digital Transformation and Risk Management on Madura Batik MSMEs - Adiati Trihastuti; Irda Agustin Kustiwi; Della Erdiana (Pusat Riset dan Inovasi Nasional, 2025)
This research investigates the impact of digital business implementation and risk management on sustainability, with accounting transparency serving as a mediating variable, within the context of Madura batik MSMEs. The central question addressed is how digital business practices and risk management contribute to enhancing sustainability through the role of accounting transparency. Employing a quantitative research design, the study utilizes Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach to examine the interrelationships among variables. The findings indicate that both digital business and risk management exert a positive influence on sustainability systems, and that accounting transparency functions as an effective mediator, reinforcing these effects. The study concludes that improved accounting transparency significantly enhances sustainabilityperformance, thereby supporting the competitiveness and long-term sustainability of Madura batik MSMEs in the digital age.